Exchange rates in multicountry econometric models - Grauwe, Paul de.; Peeters, Theo (New York : St. Martin's Press, 1983)
This book examined the role exchange rate models play in multicountry econometric models. It also assess how recent theories of exchange rate behavior have affected the way econometric model builders construct their models.
"Papers presented at the Leuven Conference on Exchange Rates in Multicountry Econometric Models (November 1981)"--Pref.
Includes bibliographies and index.
usc 30/04/18
Loans
Keywords: Foreign exchange rates; Econometric models; Foreign exchange rates--Econometric models